DEVELOPMENT OF DIGITAL HISTORICAL COMIC MEDIA TO IMPROVE LEARNING INTEREST OF GRADE XI 4 STUDENTS AT STATE SENIOR HIGH SCHOOL 1 PORONG : Pengembangan Media Komik Digital Sejarah Untuk Meningkatkan Minat Belajar Siswa Kelas XI 4 di SMA Negeri 1 Porong - J. Priyanto Widodo; Satrio Wibowo; Mila Dwi Karinah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to develop a comic of the battle of November 10, 1945 in Surabaya as a learning media in the form of a digital historical comic to increase the learning interest of class XI 4 students at SMA Negeri 1 Porong. The research method used is a development research that uses five stages, namely analysis, design, development, implementation, and evaluation known as the ADDIE development model. Based on the final results of the study, it is shown that the digital comic learning media of the history of the battle of November 10, 1945 in Surabaya is suitable for use in learning. With the following results: 1) the digital comic of the history of the battle of November 10, 1945 in Surabaya is rated "good" from the assessment of material experts, 2) the digital comic of the history of the battle of November 10, 1945 in Surabaya is rated "good" from the assessment of media experts, 3) the digital comic of the history of the battle of November 10, 1945 in Surabaya in increasing students' learning interest is rated "good" from the assessment results of students at SMA Negeri 1 Porong. The use of these media has proven to be able to attract interest and make it easier for students to understand historical material that is often considered difficult and boring. In conclusion, digital comics are an effective, innovative alternative in supporting history learning at the high school level.